2018
DOI: 10.1029/2018gc007474
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Mantle Flow System Beneath the Indochina Peninsula Revealed by Teleseismic Shear Wave Splitting Analysis

Abstract: Numerous geoscientific investigations have been conducted on the southeastern Tibetan Plateau and adjacent areas for understanding crustal and mantle deformation associated with the indentation of the Indian Plate into Eurasia. A number of key issues, such as the causes of a sudden change of fast polarization orientations from N‐S to almost E‐W at approximately 26°N revealed by shear wave splitting (SWS) studies, and the geodynamic implications of the transition still remain enigmatic, partially due to the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 48 publications
6
29
0
Order By: Relevance
“…The summary of δt is presented in Figure S1. The resulting average δt is slightly smaller than the average value (1.25 s) from oceanic islands calculated by Király et al () from the Global Splitting Database (http://www.gm.univ-montp2.fr/splitting/) (Wustefeld et al, ) but which is in reasonable agreement with previous local studies, for example, 0.90 ± 0.14 s in the southernmost Indochina Peninsula (Yu et al, ), ∼1 s in the Sumatra wedge (specifically, measurements are made for the stations located above the 150‐km slab contour) (Hammond et al, ), and 0.34–1.08 s in the Banda wedge measured from local S splitting (Di Leo et al, ). The larger δt (of 1.6–2.4 s in Sumatra, Collings et al, ; ∼1.6 s in Java, Hammond et al, ; and 1.13–1.38 s in Banda, Di Leo et al, ) has been primarily attributed to subslab mantle flow, rather than the flow in the mantle wedge, and the larger δt all comes from SKS splitting measurements.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The summary of δt is presented in Figure S1. The resulting average δt is slightly smaller than the average value (1.25 s) from oceanic islands calculated by Király et al () from the Global Splitting Database (http://www.gm.univ-montp2.fr/splitting/) (Wustefeld et al, ) but which is in reasonable agreement with previous local studies, for example, 0.90 ± 0.14 s in the southernmost Indochina Peninsula (Yu et al, ), ∼1 s in the Sumatra wedge (specifically, measurements are made for the stations located above the 150‐km slab contour) (Hammond et al, ), and 0.34–1.08 s in the Banda wedge measured from local S splitting (Di Leo et al, ). The larger δt (of 1.6–2.4 s in Sumatra, Collings et al, ; ∼1.6 s in Java, Hammond et al, ; and 1.13–1.38 s in Banda, Di Leo et al, ) has been primarily attributed to subslab mantle flow, rather than the flow in the mantle wedge, and the larger δt all comes from SKS splitting measurements.…”
Section: Resultssupporting
confidence: 91%
“…The lateral flow developed by highly arcuate subducting slab in Banda and trench‐oblique flow caused by the eastward subduction of the South China Sea Plate in Philippines will additionally contribute to the flow systems. Moreover, other flows with different geometry will certainly serve as important components in the flow systems, including nearly trench‐normal‐oriented flow (Figure ) (more likely a 2‐D corner flow) induced by the eastward subduction of the Indo‐Burman plate observed beneath the southern Indochina Peninsula (Yu et al, ); a 3‐D toroidal flow around lateral slab edges of the Celebes Sea slab suggested by Di Leo et al (); and a 3‐D toroidal flow in the Sumatra mantle wedge associated with slab tear observed by Huang et al (). The subslab mantle flow around the highly arcuate Banda slab, if it exists, may also contribute to the flow systems beneath the Sunda Plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fit is however poor (red symbols) below Southeast Asia and the central and West Mediterranean realm. A more recent investigation over Indochina (Yu et al, 2018) confirms this poor fit. When using SL2013sv's seismic anisotropy inference instead (Figure 4), the quality of the match depends upon the depth considered.…”
Section: Comparing Seismic Anisotropy and Long-term Kinematic Trajectmentioning
confidence: 91%
“…This may imply that SKS-splitting anisotropy, as it corresponds to local measurements, shows here a smaller-scale flow that is not captured by the smooth SL2013sv model. The direction of this flow could be toward the west or southwest, corresponding to a tighter counter flow around the East Himalayan syntaxis toward the Burma slab as proposed by Wang et al (2013) and Yu et al (2018). At 100 km, the flow geometry (or of shearing below the lithosphere) indicated by SL2013sv anisotropy below Asia can otherwise be compared with the model of Sternai et al (2016;Figure 4a, inset) which was designed to study the 3-D interactions between slab retreat and collision for the India-Asia collision.…”
Section: Deep Flow Patternmentioning
confidence: 92%